Wages as risk compensation in Germany - Grund, Christian (Bonn, 2000)
"The theory of compensating wage differentials is generally accepted. Still, there has been no strong or even contrary evidence for compensating wage differentials in Germany so far. Estimating wage regressions with data of the German Socio-Economic Panel (GSOEP) within individually perceived hazards of work accidents as a risk variable, evidence for compensating wage differentials in Germany is found even though other effects may partly weaken the existing wage premiums due to risks at work."